Strategi Pemasaran Pakan Ikan Berbagai Merek di Desa Sibaganding Kecamatan Girsang Sipangan Bolon Kabupaten Simalungun Provinsi Sumatera Utara - Puja Tio Casa Nola Panjaitan; Hendrik; Zulkarnaini (JURNAL SOSIAL EKONOMI PESISIR, 2021)
This research was conducted on March 9 until 25 2020 in Sibaganding Village, Girsang Sipangan Bolon Sub-District, Simalungun Regency. The purpose of this study was to determine the implementation of the marketing mix of fish feed for various brands and to determine consumer assessment of the marketing mix of fish feed for various brands in Sibaganding Village. The method used in this research is a survey method with a descriptive qualitative approach. The technique of determining respondents used purposive sampling and stratified random sampling. The results showed that the marketing mix strategy of the feed companies Comfeed, Pokhpand, Cargill and Sinta had implemented the 4P marketing mix, namely product, promotion, price and distribution. By marketing fish feed in Sibaganding Village, the company implements various 4Ps, namely, product (protein content and product variation); price level (weight of feed / packaging and type of feed); promotions (word of mouth, social media and discounts); location and distribution (company location, distributor and direct distribution). Based on consumer assessments of the 4P marketing mix applied by feed companies, namely 37% of consumers to buy fish feed products with the main choice being promotions given by the company, then 30% for products, 20% for prices and 13% for location and distribution